1993
DOI: 10.1152/ajpendo.1993.264.4.e606
|View full text |Cite
|
Sign up to set email alerts
|

Amylin and CGRP induce insulin resistance via a receptor distinct from cAMP-coupled CGRP receptor

Abstract: Amylin and calcitonin gene-related peptide (CGRP) inhibited insulin-stimulated 2-deoxyglucose uptake in L6 myocytes and isolated soleus muscle. Both peptides were maximally active at 10 pM in L6 cells and inhibited insulin action by 40-50%. In soleus muscle amylin and CGRP inhibited insulin-stimulated uptake by 65-85%. Amylin competed with 125I-CGRP for binding to L6 cells but with 100-fold lower potency than CGRP. Occupancy of the CGRP receptor in L6 cells is coupled to adenylyl cyclase. Amylin increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…Tissue-specific CGRP levels would be a more accurate measure of physiological effect of CGRP, as plasma CGRP levels might be due to spillover (22). Pre-clinical studies showed that increased pancreatic storage of CGRP results in insulin resistance (43,74). However, studies using radioimmunoassay, radio-receptor assay, and immunoradiometric assay demonstrated a strong correlation between the levels of CGRP in plasma and tissue extracts of rats and humans (22,24).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-specific CGRP levels would be a more accurate measure of physiological effect of CGRP, as plasma CGRP levels might be due to spillover (22). Pre-clinical studies showed that increased pancreatic storage of CGRP results in insulin resistance (43,74). However, studies using radioimmunoassay, radio-receptor assay, and immunoradiometric assay demonstrated a strong correlation between the levels of CGRP in plasma and tissue extracts of rats and humans (22,24).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a l-year-old Cap-Des rat has a concentration of CGRP in its blood equal to that characteristic of a five-week-old rat (38). CGRP is known to induce insulin resistance in muscle in rats, both in vivo and in vitro (5,23,35,39). Moreover, the concentration of CGRP in blood of old rats, about 70 pM (37,38), might even be capable of antagonizing the action of insulin, since a maximum inhibition of insulin-stimulated glucose uptake by soleus muscle in vitro is achieved at a peptide concentration of 10 pM (23).…”
Section: Discussionmentioning
confidence: 99%
“…CGRP is known to induce insulin resistance in muscle in rats, both in vivo and in vitro (5,23,35,39). Moreover, the concentration of CGRP in blood of old rats, about 70 pM (37,38), might even be capable of antagonizing the action of insulin, since a maximum inhibition of insulin-stimulated glucose uptake by soleus muscle in vitro is achieved at a peptide concentration of 10 pM (23). A rise in insulin resistance has been reported in old rats, starting between 2 and 4 months of age and reaching a maximum at 12 months (3,13,29,31).…”
Section: Discussionmentioning
confidence: 99%
“…Amylin increases glycogen phosphorylase activity and reduces glycogen synthase activity in skeletal muscle (Deems et al, 1991b;Young et al, 1991;Lawrence & Zhang, 1994;Pittner et al, 1995a), promoting glycogenolysis and lactate release Pittner et al, 1995a). These effects appear to be associated with activation of adenylyl cyclase (Pittner et al, 1995a); although some reports suggest that additional or alternative signalling mechanisms may be involved (Lawrence & Zhang, 1994;Deems et al, 1991a; Kreutter et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of amylin and CGRP have been studied in two skeletal muscle cell lines, rat L6 cells and mouse C2C12 cells. Rat L6 cells appear to express CGRP receptors coupled to adenylyl cyclase activity (Kreutter et al, 1989(Kreutter et al, , 1993Zhu et al, 1991;Poyner et al, 1992); these receptors are activated by amylin with low potency relative to CGRP (Zhu et al, 1991;Poyner et al, 1992). However, potent effects of amylin have also been reported in C2CI2 cells (Sheriff et al, 1992).…”
Section: Introductionmentioning
confidence: 99%